PENGUKURAN NILAI TUKAR NELAYAN DI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Edy Budiono; Idiannor Mahyudin; A. Riswandi Bandung (Fish Scientiae, 2019)
Purpose of the research was to measure trade turn and economic welfare of fisherman living in the Sea Land Regency South Borneo Province. The research use descriptive method in valving that primary data were obtained by survey and secondary data oven collected from relevant government agencies. Exchange rate index of threatmen was measured during 4 months (November 2012 – February 2013). Index formulation was developed Laspeyres the economic welfare of the fisherman.Analysis of fisherman trade term found 6 formulation, in cloding (1) NTN-owner (2)NTN-individual (3)-NTN squire (4) NTN-skilled crew (5) NTN-ordinary crew and (6)NTN-traditional. Research results showed that NTN for Tanah Laut district was above100 and INTN was above 1. Eventhough economic welfare of fisherman was increase.